2015
DOI: 10.1007/s00432-015-2023-1
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of pSTAT3 in gastric cancer: a meta-analysis

Abstract: In conclusion, our meta-analysis suggests that positive expression of pSTAT3 is associated with poor prognosis in gastric cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Activated STAT3 protein acts as a transcriptional factor to regulate cell proliferation, apoptosis, angiogenesis, tumor invasion and metastasis [35]. A metaanalysis confirmed that high expression of p-STAT3 was associated with poor prognosis of GC [36]. In addition, clinical usage of a STAT3-regulated micro-RNA signature showed a prognostic potential in early GC stratification [37].…”
Section: Discussionmentioning
confidence: 99%
“…Activated STAT3 protein acts as a transcriptional factor to regulate cell proliferation, apoptosis, angiogenesis, tumor invasion and metastasis [35]. A metaanalysis confirmed that high expression of p-STAT3 was associated with poor prognosis of GC [36]. In addition, clinical usage of a STAT3-regulated micro-RNA signature showed a prognostic potential in early GC stratification [37].…”
Section: Discussionmentioning
confidence: 99%
“…Activation of STAT3 transcription activity induces the expression of a wide range of target genes promoting key pro-oncogenic cellular functions, such as inflammation, proliferation, survival, invasion, and angiogenesis 28 . STAT3 is activated by phosphorylation of the Y705 position, followed by nuclear translocation of the phosphorylated proteins with subsequent activation of the transcription of specific downstream genes and metastasis of cancers 29 . Our results demonstrated decreased mRNA expression levels in GC cells featuring STAT3 knockdown and downregulation of several STAT3 target genes, such as MMP-2, MMP-14, VEGF-C, VEGF-D, and HGF.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study on intrahepatic cholangiocarcinoma found that patients with high STAT3 expression levels had a poor overall and disease-free survival [53]. After analyzing a large number of gastric cancer cases, both STAT3 and p-STAT3 were shown to be associated with an increased mortality risk [54,55]. In another study, Deng et al reported that 62.6% (67/107) and 38% (41/107) of gastric cancer tissues exhibited positive immunostaining for STAT3 and p-STAT3, respectively [56].…”
Section: Leptin Biology and Molecules Of Relevant Signal Transductmentioning
confidence: 99%